Strategi Pembangunan Desa Wisata untuk Peningkatan Kesejahteraan Masyarakat: Studi Kasus Desa Bi’ih, Kalimantan Selatan - Mima Artamevia; Muharman Lubis; Iqbal Yulizar Mukti (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Tourism managed and developed by the local community is one of the main pillars in realizing sustainable rural economic development. This study aims to analyze the development strategy of Bi'ih Tourism Village, Banjar Regency, South Kalimantan, in improving community welfare through the integration of the Community-Based Tourism (CBT) concept and a digital approach. In this study, the method used is descriptive qualitative with primary data collection through interviews with the Village Head, BUMDes administrators, youth organizations, MSME actors, and local tourists, as well as secondary data from village profile documents and Tourism Office reports. The results of this study indicate that Bi'ih Village has opportunities in developing durian agrotourism and preserving Banjar culture, but still faces obstacles in terms of digital promotion, technological literacy, and information media management. The implementation of strategies that combine community participation, digital literacy training, and revitalization of village promotional media is expected to strengthen the image of the destination while increasing community income. The integration of CBT with Smart Tourism can create an inclusive, adaptive, and sustainable tourism management model. This research also provides implications for other villages in South Kalimantan to adopt a similar approach as an effort to strengthen the local economy based on digital innovation and cultural wisdom.